INTRA-SENTENTIAL SWITCHING USE IN CLASSROOM ACTIVITY - Muji Adi Mujiono; Thalia Medina Diputri (PROJECT (Professional Journal of English Education), 2018)
The research focused in the intra-sentential code switching used by the students in English Department of IKIP Siliwangi Bandung. The research was conducted to find out the intra-sentential switching that used by the students, why the students switch code, and the function of intra-sentential switching in classroom activity. The research employed a qualitative descriptive study involing field research. The samples are 3 groups presentation from class A2 English Education 2015 IKIP Siliwangi Bandung. This study explored pattern of intra-sentential code-switching (CS) that are manifest in classroom activity of English-Indonesia-Sunda in class A2 English Education 2015 IKIP Siliwangi Bandung, the reason why students switch thier code and in what situation students switch their code or language. The result of this research are 3 groups presentation were switching their language in type of intra-sentential switching, the reasons they switch their langugae are less vocabulary, to make they easier to express their mind, to make listener or audience easier to understand, and nervous. In presentation, group discussion, speech & daily conversation are situations they switch their code or language.Keywords:   Code switching, Intra-sentential switching, classroom activity.